Developing Small and Medium-Sized Enterprises (SMEs) Taxonomy in Malaysia (Malaysian Management Journal, 2000)
In most economies, small and medium-sized enterprises (SMEs) consitute a variety of different firms encomÂpassing a wide range of industries. SMEs are heterogeneous: they differ at least in terms of their capabilities, stage of development, resources as well as requirements. The heterogeineity ofSMEs suggests that any systematic and rigorous attempt. to understand, explain and predict their behaviour should begin with the development of a taxonomy for them. A taxonomy provides a means for grouping and defining heterogenous SMEs - understandÂing their similarities and differences, their strengths and weaknesses. In the literature, several attempts to develop SMEs taxonomies have been made. Upon examining three of these taxonomies, it is found that SMEs can be classified in a number of different ways. Nonetheless, whilst this review of taxonomies literature is insightful in developing our own SMEs taxonomy, a careful study of the various features of SMEs is awaited if we were to develop a comprehensive taxonomy for the Malaysian SMEs.